Skin-derived vascularized lymph node transfer combining with liposuction in stages for bilateral lower extremity lymphedema: a case report - Pan, Wenjie; Wang, Liangliang; Wei, Miaomiao; Wu, Xiangkui; Li, Hai; Wu, Bihua; Xiao, Shune; Deng, Chengliang (Frontiers in Oncology, 2025)
Bilateral lower extremity lymphedema (LEL) significantly impairs patients’ quality of life. A 66-year-old female patient, who developed bilateral LEL following cervical cancer surgery (classified as International Society of Lymphology stage II), presented to our hospital. In a two-stage surgical approach, we employed two distinct lymph node transfer techniques: (1) transplantation of a 7 × 2 cm vascularized lymph node flap harvested from the right supraclavicular region to the left popliteal fossa, and (2) transplantation of a 9 × 3 cm skin-derived lymph node flap obtained from the submental area to the right popliteal fossa. Both procedures were combined with liposuction. Postoperative management included compression therapy, with no complications observed during the recovery period. The patient demonstrated significant improvement in quality-of-life measures. Lymphoscintigraphic imaging at the 12-month follow-up revealed improvement in lymphatic function, showing volume reductions of 2129.28 mL (left lower limb) and 1699.65 mL (right lower limb). No recurrence of swelling was reported during the 30-month follow-up period. This case suggests that a two-stage approach combining vascularized lymph node transfer (VLNT) with liposuction may represent an effective treatment strategy for bilateral lower extremity lymphedema.